2022
DOI: 10.3389/fpubh.2022.1019691
|View full text |Cite
|
Sign up to set email alerts
|

Mapping knowledge landscapes and emerging trends of the links between osteoarthritis and osteoporosis: A bibliometric analysis

Abstract: BackgroundOsteoarthritis has the characteristics of degenerative changes in articular cartilage and secondary osteoporosis, and it is a common chronic irreversible joint disease. In addition to affecting articular cartilage, subchondral bone, joint capsule and synovial membrane also undergo pathological changes during the development of the disease. Multiple studies have revealed that patients with osteoarthritis were found to have a significantly increased risk of osteoporosis, which also contributes to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…This global trend is corroborated by various bibliometric studies related to osteoporosis, all demonstrating a similar pattern with different research leaders. [22–26]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This global trend is corroborated by various bibliometric studies related to osteoporosis, all demonstrating a similar pattern with different research leaders. [22–26]…”
Section: Discussionmentioning
confidence: 99%
“…This global trend is corroborated by various bibliometric studies related to osteoporosis, all demonstrating a similar pattern with different research leaders. [22][23][24][25][26] On the other hand, when adjusting the number of publications throughout the years of study, it was identified that on average only 5 countries had 5 or more publications per year.…”
Section: Annual Publicationsmentioning
confidence: 99%
“…However, the relationship between KOA and OP is still highly controversial. In recent years, with continuous research, the following three views broadly exist: the first view is that there is a positive correlation between the two, i.e., OP can lead to the occurrence of KOA [2] ; the second view is that there is a negative correlation between the two, i.e., the presence of KOA causes bone growth and thus reduces the occurrence of OP [3] ; and the third view is that there is no correlation between the two [4] . However, most studies support a strong correlation between KOA and OP [5] .…”
Section: Introductionmentioning
confidence: 99%